PENGARUH METODE MIND MAPPING DALAM MENULIS KOMPREHENSIF UNTUK MAHASISWA KESEHATAN MASYARAKAT DI INSTITUT KESEHATAN MEDISTRA LUBUK PAKAM - SULASTRI BR GINTING; TEDTY ROHAYA TINAMBUNAN (Jurnal Penelitian Keperawatan Medik, 2022)
The goal of this research is finding and describing the effect of mind mapping on writing skill for Public Health students Health Institute of Medistra Lubuk Pakam. The research study used a quasi-experimental study. A total of 64 students came from two different groups, Class A (32 students) as the experimental group and Class B (32 students) as the control group. The students in the experimental group used rational teaching, and the students in the control group used conventional technical teaching. Analyze data using pre- and post-tests. The experimental group and the control group were pre-tested before treatment, and post-test was carried out after treatment. Data from pre- and post-tests were examined using descriptive and inferential statistics. After the data were tested and found to be homogeneous and normal, the hypotheses were tested using SPSS (Statistical Package for the Social Sciences). The research result shows the difference when students write by using mind mapping and students write by not using mind mapping in the writing ability. The result can be seen by hypothesis testing through SPSS (Statistical Package for The Social Sciences). Significance values ​​were greater than the significance level of 0.01 (<0.05), which meant that the data from this study were considered not significantly different. Therefore, the hypothesis of this study was confirmed. It can be concluded that mind mapping significantly improves students' writing ability for health students at Health Institute of Medistra Lubuk Pakam.